Effects of oxytetracycline on aerobic granular sludge process: Granulation, biological nutrient removal and microbial community structure. (November 2022) - Nivedhita, S.; Shyni Jasmin, P; Sarvajith, M.; Nancharaiah, Y.V.
Abstract: Formation of aerobic granular sludge (AGS), process performance and microbial community structure were investigated in lab-scale sequencing batch reactors (SBR) operated without and with oxytetracycline (OTC). Granulation of activated sludge and appearance of AGS was observed in parallel SBRs operated without and with OTC. However, formation of well-settling aerobic granules was relatively faster in the SBR fed with 100 μg/L OTC and observed within 2 weeks of start-up. Ammonium, total nitrogen, and phosphorus removals were quickly established in the AGS cultivated without OTC. In contrast, nitrogen and phosphorus removals were lower in the OTC fed SBR. But, a gradual improvement in nitrogen and phosphorus removals was observed. After 45 days, nitrogen and phosphorous removals were stabilized at 99% and 70%, respectively, due to establishment of OTC-tolerant community. qPCR revealed the impact of OTC on ammonium oxidizing bacteria, polyphosphate accumulating organisms and their enrichment during exposure to OTC. Ammonium and phosphorus were majorly removed via nitritation-denitritation and enhanced biological phosphorus removal (EBPR) pathways, respectively, in the presence of OTC. Brevundimonas (35%), Thaurea (14%) sp. Ca . Competibacter (5.6%), and Ca . Accumulibacter (4.2%) were enriched in OTC-fed AGS. Of the two OTC-tolerant strains isolated, Micrococcus luteus exhibited growth and efficient OTC biotransformation at different OTC concentrations. Moreover, M. luteus was predominantly growing in the form of aggregates. Key traits such as tolerance, biotransformation and high autoaggregation ability allowed a niche for this strain in the granules. This work has important implications in understanding the effect of antibiotics on AGS and designing AGS based treatment for antibiotic-laden wastewaters. Graphical abstract: Image 1 Highlights: Aerobic granular sludge exhibited 35% higher oxytetracyline removal than activated sludge. Oxytetracycine (OTC) removal was sustained by biotransformation and required carbon substrate. Abundance of AOB and PAOs was decreased upon exposure to oxytetraclyine. Nitrogen and phosphorus removals were >99% and 70%, respectively, in OTC fed SBR. Micrococcus luteus grew as aggregates and exhibited OTC biotransformation potential.